2021
DOI: 10.1111/jdi.13680
|View full text |Cite
|
Sign up to set email alerts
|

Placental expression of glucose transporters GLUT‐1, GLUT‐3, GLUT‐8 and GLUT‐12 in pregnancies complicated by gestational and type 1 diabetes mellitus

Abstract: Aims/Introduction: The aim of the present study was to evaluate the placental expression of glucose transporters GLUT-1, GLUT-3, GLUT-8 and GLUT-12 in term pregnancies complicated by well-controlled gestational (GDM) and type 1 pregestational diabetes mellitus (PGDM). Materials and Methods: A total of 103 placental samples were obtained from patients diagnosed with GDM (n = 60), PGDM (n = 20) and a non-diabetic control group (n = 23). Computer-assisted quantitative morphometry of stained placental sections was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…GLUT12 protein expression was mainly pronounced in the first trimester syncytial and extravillous trophoblast cells and term villous vascular smooth muscle cells, villous stromal cells and trophoblast cells of the chorion [ 80 , 81 ]. Further, Stanirowski et al confirmed GLUT8 and GLU12 protein expression in the term placental tissue by immunohistochemistry [ 82 , 83 ].…”
Section: Glucose Transport In the Human Placentamentioning
confidence: 99%
See 3 more Smart Citations
“…GLUT12 protein expression was mainly pronounced in the first trimester syncytial and extravillous trophoblast cells and term villous vascular smooth muscle cells, villous stromal cells and trophoblast cells of the chorion [ 80 , 81 ]. Further, Stanirowski et al confirmed GLUT8 and GLU12 protein expression in the term placental tissue by immunohistochemistry [ 82 , 83 ].…”
Section: Glucose Transport In the Human Placentamentioning
confidence: 99%
“…Both PGDM and GDM patients treated with insulin had significantly increased GLUT4 and GLUT9 protein expression compared to healthy controls [ 120 ]. Finally, there were no differences in the GLUT3, GLUT8, and GLUT12 protein expression in patients with PGDM and control pregnant women [ 82 ].…”
Section: Placental Glucose Transport In Patients With Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered GLUT1 expression is discovered in pathological pregnancies, implicating abnormal glucose usage. Available documents suggest that GLUT1 was increased in HIP with or without a large infant [ 8 , 9 , 10 , 11 , 12 , 13 ]. In contrast, its expression is shown to be decreased in IUGR [ 14 ].…”
Section: Introductionmentioning
confidence: 99%